Ecology of fresh waters : - Moss, Brian (Blackwell Science, 1998)
This established textbook continues to provide a comprehensive and stimulating introduction to rivers, lakes and wetlands, and was written as the basis for a complete course on freshwater ecology. Designed for undergraduate and early postgraduate students who wish to gain an overall view of this vast subject area, this accessible guide to freshwater ecosystems and man's activities will also be invaluable to anyone interested in the integrated management of freshwaters. The author maintains the tradition of clarity and conciseness set by previous editions, and the text is extensively illustrated with photographs and diagrams. Examples are drawn from the author's experience in many parts of the world.